Bioinformatics Analysis of Functional Relations Between CNPs Regions - Dave, Kirtan; Banerjee, Atreyi (Current Bioinformatics, 2011)
Genes showing copy number variation have been the subject of much study in recent years. Copy number variation has been found to be surprisingly common among humans. As much as 12% of the human genome is polymorphic in copy number and this can disrupt genes and alter gene dosage to influence gene expression, phenotypic variation and adaptation, but little is known about the significance of these copy number polymorphic genes. On-line databases, Complex Networks software, Gene Ontologies (GOs) analysis web servers, and other Bioinformatics tools may be very useful in this branch. In this sense, the present work reviews some bioinformatics concepts and previous studies related to Complex networks, GOs, and related methods that can be used for the study of Copy Number Polymorphic regions. The second objective of the envisaged work was to trace the divergence of human genomes in copy number variant genes and ascertain three conditions disease pathways and Functional Categories with Whole Genome TilePath (WGTP) array and 500K early access (500KEA) array data. These tests were performed to see significant departures from the divergence/ polymorphism ratio. The analysis of genes from WGTP and 500KEA gave the evidence for reciprocal disease and their pathways.
Keywords: Whole Genome TilePath